2019
DOI: 10.3390/app9173533
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Doors Closed as One Reason for Fatigue in Teenagers—A Case Study

Abstract: (1) Background: Healthy teenagers are often sleepy. This can be explained by their physiology and behavioral changes; however, the influence of CO2 concentration above 1000 ppm should not be neglected with respect to sleep dissatisfaction. (2) Methods: CO2 concentrations were measured in two similar bedrooms occupied by girls aged 9 and 13 years old. The scheme of measurements included random opening and closing of the bedroom doors for the night. Additionally, the girls evaluated their sleep satisfaction in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Results for six measurements are shown in Table 5. The slope of linear dependence of the corrected CO2 concentration increases with higher occupant density and ACH, but when CO2 gains are calculated from this slope similar values are obtained in all cases from 0.0043 to 0.0048 L/s, and agree with the theoretical value of Table 1 for young university students (18)(19)(20)(21)(22)(23)(24)(25) year old) with sedentary activity (M = 1.3 MET) with similar male and female contribution. The study of the method reproducibility in the workshop classroom, shows a high discrepancy between the results of both measurements (0.044 vs. 0.048 L/s).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Results for six measurements are shown in Table 5. The slope of linear dependence of the corrected CO2 concentration increases with higher occupant density and ACH, but when CO2 gains are calculated from this slope similar values are obtained in all cases from 0.0043 to 0.0048 L/s, and agree with the theoretical value of Table 1 for young university students (18)(19)(20)(21)(22)(23)(24)(25) year old) with sedentary activity (M = 1.3 MET) with similar male and female contribution. The study of the method reproducibility in the workshop classroom, shows a high discrepancy between the results of both measurements (0.044 vs. 0.048 L/s).…”
Section: Resultssupporting
confidence: 83%
“…It is worth noting that CO 2 concentration is often found above recommendations in buildings with high people density and insufficient ventilation, especially schools [10][11][12][13][14][15][16][17]. Problems with CO 2 concentration in residential buildings were discussed by Mainka et al, [18].Nowadays, the ASHRAE (American Society of Heating, Refrigerating and Air Conditioning Engineers) standard [19] recommends indoor CO 2 concentrations less than 700 ppm above the outdoor concentration, giving also a guideline of 1000 ppm. Thus, the CO 2 recommended level is significantly lower than several years ago.…”
mentioning
confidence: 99%
“…A study conducted in Poland during the sleeping period of one female teenager (Mainka and Zajusz-Zubek, 2019) showed that CO 2 levels of 6000 mg m À3 were reached several times, when the bedroom's door was closed. Another study carried out in Chinese student dormitories reported a mean CO 2 steady value of 3150 mg m À3 during sleep and associated levels above 3384 mg m À3 with worse IAQ satisfaction (Zhang et al, 2018).…”
Section: Carbon Dioxidementioning
confidence: 99%
“…Two more studies have worked on the evaluation of the indoor environment quality while focusing on a specific population group: Children and teenagers. The study of Mainka A. and Zajusz-Zubek E., [8] named 'Keeping Doors Closed as One Reason for Fatigue in Teenagers-A Case Study' investigated the variability of CO 2 concentration in naturally ventilated bedrooms of teenagers in Polland, by correlating bedroom door opening during the night with CO 2 concentration and thermal comfort. In the study 'Cooking/Window Opening and Associated Increases of Indoor PM2.5 and NO 2 Concentrations of Children's Houses in Kaohsiung, Taiwan', Yen Y. et al [9] attempted to assess the influence of window opening and cooking activity to measured air pollutants levels in 60 children homes in an industrial city in Taiwan.…”
Section: From Indoor Environment Quality Perception To Indoor Air Quamentioning
confidence: 99%